Using Lyman-α to probe the interior and edges of the heliosphere - Mayyasi, Majd; Quémerais, Eric; Katushkina, Olga; Clarke, John; Izmodenov, Vlad; Brandt, Pontus; Sokol, Justyna; Linsky, Jeffry; Baliukin, Igor (Frontiers in Astronomy and Space Sciences, 2022)
Understanding the role of neutral atoms in the heliospheric interface (between the bow shock and heliopause) is critical to identifying dynamics within our local bubble. This article recommends building upon existing measurements with new, high-spectral resolution observations of H Lyman-a, from a heliospheric mapping mission, to resolve the momentum exchange in reactions between the Solar Wind and Energetic Neutral Atoms that are key to identifying the most important heliospheric processes.